Biodiversity of Medicinal Plants in Tawang Serimbak Forest, Ensaid Panjang Village, Sintang Regency - Fathul Yusro; Gusti Hardiansyah; Erianto Erianto; Yeni Mariani; Aripin Aripin; Hendarto Hendarto; Denni Nurdwiansyah (Universitas Mataram, 2020)
Non-forest estate (APL) such as Tawang Serimbak need to be maintained because they store various flora that is useful for human life, one of which is medicinal plants. The research objective is to identify, analyze the potential, and to know the protection status of medicinal plants found in the Tawang Serimbak forest. The method of research were making a 100x100 m (square) cluster. At the center of the square placed a circular plot within 0.1 Ha (0.5 Ha of each cluster). Four circular subplots were made in each plot consisting of 1 m radius seedling subplot, 2 m for stake subplot, pole subplot (5 m radius), and 17.8 m for tree subplot. Data of species, efficacy, and protection status (IUCN) were identified, and the potency of plants were analyzed using plants density (number of plants/Ha). Tawang Serimbak forest has been identified as having 49 species of medicinal plants. Some species have great potentials such as Galearia fulva, Shorea uliginosa, and Alseodaphne sp. A total of 9 species of medicinal plants were identified in protected status, two of which were endangered; namely, Lithocarpus maingayi, Shorea uliginosa, and one other species with Endangered (critical) status, namely Santiria rubiginosa. Protection of forests in APL by the community can maintain the biodiversity of medicinal plants. The existence of the Tawang Serimbak forest needs to be protected and turned into a forest with high conservation value (HCV).